2022
DOI: 10.55446/ije.2022.524
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of Leucinodes orbonalis Guenee from Manipur

Abstract: Leucinodes orbonalis Guenée (Lepidoptera: Crambidae) is a serious pest of brinjal. During the field observations, a solitary larval parasitoid of L. orbonalis viz., Trathala flavoorbitalis (Cameron) (Hymenoptera: Ichneumonidae) was osberved. The present study reports larval parasitism of L. orbonalis with 6% field parasitism by T. flavoorbitalis in Manipur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…T. flavororbitalis has been recorded as an important parasitoid in different countries, such as USA ( Swezey, 1926 ), Bangladesh ( Alam & Sana, 1962 ), Nepal ( Kafle, 1970 ) and Sri Lanka ( Sandanayake & Edirisinghe, 1992 ). It has been observed in different regions of India, Haryana ( Naresh, Malik & Balan, 1986 ); Bihar ( Mallik et al, 1989 ) ; Karnataka ( Ranjith et al, 2020 ); Gujarat, Uttar Pradesh ( Alam et al, 2003 ); and Manipur ( Thokchom et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. flavororbitalis has been recorded as an important parasitoid in different countries, such as USA ( Swezey, 1926 ), Bangladesh ( Alam & Sana, 1962 ), Nepal ( Kafle, 1970 ) and Sri Lanka ( Sandanayake & Edirisinghe, 1992 ). It has been observed in different regions of India, Haryana ( Naresh, Malik & Balan, 1986 ); Bihar ( Mallik et al, 1989 ) ; Karnataka ( Ranjith et al, 2020 ); Gujarat, Uttar Pradesh ( Alam et al, 2003 ); and Manipur ( Thokchom et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trathala flavoorbitalis , a widely recognized parasitoid of L. orbonalis , has been observed in different regions of India, especially Bihar, Tamil Nadu, Manipur and Karnataka ( Mallik et al, 1989 ; Yasodha & Natarajan, 2009 ; Murali et al, 2017 ; Ranjith et al, 2020 ; Thokchom et al, 2022 ). This parasitoid species has a cosmopolitan distribution, and is known from the Afrotropical, Autralasian, Eastern Palaearctic, Indomalayan, Nearctic, and Oceanic regions ( Rousse & Villemant, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the observation of Ardez et al (2008), Das and Patnaik (1971) found the species boring into tomato fruits and shoots in the wild, and, like Boopal et al (2013), successfully reared larvae to adults on tomato fruits in the lab. Lab-reared L. orbonalis also successfully completed their life cycle in the study of Jethva and Vyas (2009), but it is not clear from the study on which part of the tomato plant (stem/fruits) the larvae were feeding. Due to the paucity of literature reporting L. orbonalis infestations on tomato in Asia as well as the absence of interceptions of L. orbonalis from tomato fruit imported from Asia, tomato is not considered as a pathway for entry (Table B.…”
Section: Biology Of Leucinodes Orbonalismentioning
confidence: 99%
“…Das & Patnaik (1971) successfully reared L. orbonalis on the fruits of S. lycopersicum (tomato), with a somewhat lower fecundity of the resulting females as compared to S. melongena; they furthermore state that in Bhubaneswar (India), the larvae were observed to also bore into the shoots of tomato plants. Jethva and Vyas (2009) conducted laboratory rearings on tomato, but they did not specify the plant tissue they provided the larvae for feeding. Maureal et al (1982) observed a longer developmental period, higher mortalities especially in later larval instars, and a shorter adult lifespan in specimens reared on tomato fruits as compared to specimens reared on eggplant.…”
Section: As Tablementioning
confidence: 99%
See 1 more Smart Citation